Perbedaan Tingkat Activity of Daily Living (ADL) antara Lansia Aktif dengan Lansia Tidak Aktif Melakukan Kunjungan - Maria Srisuharny; Maria Diyah; Erni Yohani Mahtuti (PROFESSIONAL HEALTH JOURNAL, 2020)
Increasing one's age will be followed by various changes that will affect the physical and psychological conditions. The older is a person, the more his physical abilities will decline causing the elderly to become dependent on others, including in meeting their ADL needs. Activity of Daily Living (ADL) is a form of measuring one's ability to do ADL independently, which includes bathing, eating, toileting, continents, dressing, and moving. The purpose of this research is to know the differences in the level of Activity of Daily Living (ADL) between the active elderly and the elderly doesn't actively visits to the elderly posyandu in the Tunggulwulung Village of Lowokwaru District. This study used an observational method with a cross sectional approach. The sample in this study amounted to 50 respondents (25 active elderly and 25 inactive elderly). The technique in this study used a purposive quota sampling with analysis of the data using the Chi-Square test. From the research result is obtained ρ: 0,006 ; α: 0,05. Because ρ<α, Ho is rejected, meaning that there is a significant difference in the level of activity of daily living between the active elderly and the elderly doesn’t actively visits to the elderly posyandu. The results of this study are expected to provide motivation to the elderly that making visits to the elderly posyandu is a fom of activity to control, maintain, and improve the health to the elderly which is held once a month at the local posyandu.